(untitled) (Global Journals of Research in Engineering, 2013)
This paper represents the difference between conventional process and modified process in pyrolysis technology. In this experiment it was tried to lessen the fuel cost and energy consumption using a parabolic solar collector, some side glasses and some magnifying glasses to concentrate sun beams and magnify the solar intensity for heating up the opaque reactor. The energy consumption in the conventional process was obtained as 9900000 J. The energy consumption obtained in case of modified pyrolysis process using solar energy was 7290000 J. Hence, the energy consumption was lessened by modified process by 26% than the conventional process. Here physical analysis of obtained oil has also been shown to determine the possibility of using it in diesel engine.